Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1371/journal.ppat.1004492
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Host Lifespan and Pathogen Reservoir Potential: An Analysis in the System Arabidopsis thaliana-Cucumber mosaic virus

Abstract: Identification of the determinants of pathogen reservoir potential is central to understand disease emergence. It has been proposed that host lifespan is one such determinant: short-lived hosts will invest less in costly defenses against pathogens, so that they will be more susceptible to infection, more competent as sources of infection and/or will sustain larger vector populations, thus being effective reservoirs for the infection of long-lived hosts. This hypothesis is sustained by analyses of different hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 67 publications
2
48
0
Order By: Relevance
“…However, whether high incidence of mixed virus infections could be linked to the plants’ perennial or annual lifecycle requires further study. For example, an annual grass species with less resistance to virus infection showed a high potential of acting as a reservoir of a generalist plant virus that also infects perennial grass hosts growing in the same habitat [2, 7679]. Furthermore, co-infection by a group of vectored viral pathogens is highest with abundant generalist vectors (which are able to transmit multiple virus species/strains), weak cross‐protection and co-infection–induced mortality [75, 80].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether high incidence of mixed virus infections could be linked to the plants’ perennial or annual lifecycle requires further study. For example, an annual grass species with less resistance to virus infection showed a high potential of acting as a reservoir of a generalist plant virus that also infects perennial grass hosts growing in the same habitat [2, 7679]. Furthermore, co-infection by a group of vectored viral pathogens is highest with abundant generalist vectors (which are able to transmit multiple virus species/strains), weak cross‐protection and co-infection–induced mortality [75, 80].…”
Section: Discussionmentioning
confidence: 99%
“…For each run, 0.5–3 ng of total RNA was added to the Brilliant III Ultra‐Fast SYBR ® Green qRT‐PCR Master Mix according to the manufacturer's recommendations (Agilent Technologies) in a final volume of 10 μl. Each plant sample was assayed in triplicate on a Light Cycler 480 II real‐time PCR system (Roche) and relative levels of gene expression were deduced from standards as previously described (Hily et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…the rest of the life span after stage 6.0 until senescence). Rosette relative growth was estimated as previously described (Hily et al ., ), and the number of rosette leaves was determined at flowering time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant longevity is an example of one such parameter that can play a role on vector fitness. Hily et al (2014) showed that CMV-infected Arabidopsis plants with a short-lived genotype supported larger M. persicae populations and were more susceptible to infection than plants with a long-lived genotype, with consequences for their role as pathogen reservoirs.…”
Section: Indirect Vector Manipulationmentioning
confidence: 99%